Growth Rate of Acropora formosa and Montipora digitata Transplanted on Biorock in Gili Trawangan - Damayanti, Luh Putu Ayu; Ahyadi, Hilman; Candri, Dining Aidil; Sabil, Abdus (Journal of Indonesian Coral Reefs, 2011)
Gili Trawangan has a high diversity of coral reefs and is one of the Aquatic Parks in Eastern Indonesia. This diversity has begun to be threatened by the human activities and natural disaster due to climate change. So we needed to start doing some rehabilitation projects. The creation of Biorock is one of coral rehabilitation method which can increase growth rate of coral. This study was to determine the growth rate of colonies of Acropora formosa and Montipora digitata growing on Biorock substrate and away (up to 10 meters) from Biorock substrate.This study was conducted in Gili Trawangan from April to August 2011, and used a method of direct measurement on colony height. The result of t-test analysis showed a significant difference between the coral growth on the Biorock substrate and outside Biorock substrate. The height of A. formosa colonies transplanted on Biorock substrate (0.43 cm/week) is around four times faster than that outside of Biorock substrate (0.09 cm/week). The growth of a M.digitata colonies on Biorock was 0.3009 cm/week while outside Biorock at was 0.009 cm/week.